OPTIMASI DIGITALISASI MARKETING PADA UMKM SAPU DI DESA SINDANGHEULA KECAMATAN PABUARAN KABUPATEN SERANG - Rahadian Arief; Bambang Dwi Suseno; Encep Saefullah; Ahmad Mukhlis; Dedy Khaerudin (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2023)
The Community Partnership Empowerment Program (PKM) aims to optimize the digitalization of marketing and sales of Micro, Small and Medium Enterprises (MSMEs) products in Sindangheula Village, Pabuaran District, Serang Regency. In this program, the main target partners are broom MSME actors. The approach used is a participatory, reflective and innovative approach, which aims to achieve increased partner competitiveness and increase their knowledge and skills in the field of Digital Marketing products. The expected results of this program include increasing the sales volume of MSME broom products and expanding market segmentation. By implementing a positive approach, this program is expected to have a positive and meaningful impact on MSME partners. Through this approach, it is hoped that small businesses can feel motivated and confident in facing complex marketing challenges in the ever-evolving digital era. A better understanding of digital marketing strategies can help MSME partners optimize their online presence, reach a wider audience and increase sales.